Heart rate variability: A biomarker of frailty in older adults? - Arantes, Flávia Sousa; Rosa Oliveira, Vinicius; Leão, Aime Karla Moraes; Afonso, João Pedro Ribeiro; Fonseca, Adriano Luis; Fonseca, Daniela Rosana Pedro; Mello, Diego Antonio C. Pina Gomes; Costa, Ivan Peres; Oliveira, Luiz Vicente Franco; da Palma, Renata Kelly (Frontiers in Medicine, 2022)
Frailty is a state of critical loss of physiological complexity resulting in greater vulnerability to stressors and has been characterized as a debility syndrome in the older adult’s population. Changes in functional capacity and in the cardiovascular system during aging are the most significant and relevant for the elderly, including the clinically healthy. In this sense, this review aims to investigate methods to monitor the performance of the older adults, such as heart variability and verify how it can be related to frailty. Therefore, understanding the heart variability changes can be a marker for frailty in older adults.